Vinyl-aziridines and cyclopropanes in Pd-catalyzed (3+2)-cycloaddition reactions with cyclic N-sulfonyl imines - Spielmann, Kim; Tosi, Eleonora; Lebrun, Aurélien; Niel, Gilles; van der Lee, Arie; de Figueiredo, Renata Marcia; Campagne, Jean-Marc (Tetrahedron, 2018)
Efficient palladium-catalyzed (3 + 2)-cycloaddition reactions of cyclic N-sulfonyl imines and vinyl-aziridines (or cyclopropanes) have been achieved. The reactions, with either vinylic substrate, proceed with excellent yields affording highly functionalized imidazolidine and pyrrolidine derivatives. The cycloadditions take place via the reaction of zwitterionic π-allyl palladium intermediates with cyclic N-sulfonyl imines through i) the formation of two NC bonds in the presence of vinylaziridines (synthesis of imidazolidines) and ii) one CC bond and one NC bond in the presence of vinylcyclopropanes (synthesis of pyrrolidines). Following on preliminary works on the diastereoselective synthesis of imidazolidines, herein we wish to give a broader view on the subject by describing derivatization reactions and attempts towards an enantioselective version. Moreover, we describe and discuss the behavior of each vinylic substrate (aziridine or cyclopropane) on the (3 + 2)-cycloaddition reactions. Mechanistic and (intriguing) selectivity outcomes are also going to be discussed. [Display omitted]